THE CORRELATION BETWEEN STUDENTS’ ATTITUDES TOWARDS PEER REVIEWING WITH THEIR WRITING PROFICIENCY - Rully Raslina Novianti (Jurnal Bahasa Inggris Terapan, 2016)
This research mainly discusses the correlation between students’ attitudes towards peer reviewing with their writing proficiency to the 1st year English Department students of STKIP Subang in Writing for General Purposes Subject. The population of this study is the 1st semester English Department students on STKIP Subang. And there are 62 students as sample chosen through simple random sampling. There are two variables used in this study: the students’ mid-term examination writing score and the result of students’ responses in questionnaires. Correlational Design which is commonly used subset of Ex Post Facto Design is chosen in this study since it tends to look at the type and/or degree of relationship between two variables. The study finds that there is a positive correlation, although there is no significant correlation between students’ attitudes toward peer reviewing with their writing proficiency. This study also divides students’ attitudes of peer reviewing into three categories; students that like to do peer editing, both like and dislike it (neutral), and they that dislike it. Key Words: student’s attitudes, peer reviewing, writing proficiency